DAYA SAING BUDIDAYA AYAM RAS PEDAGING PADA BERBAGAI POLA USAHA - Herawati, Maria; Haryono, Dwi; Lestari, Dyah Aring Hepiana (Jurnal Ilmu-Ilmu Agribisnis, 2016)
The purpose for this research is to know the implementation partnership in broiler chicken farming with contract agreement and verbal agreement, to analyze the competitiveness broiler chicken farming and to analyze sensitivity of competitiveness due to changes in price of input and output.  The data was analyzed by descriptive qualitative using PAM (Policy Analysis Matrix) analysis model and elasticity.  The result showed that private profit of autonomous pattern was Rp2,582,549 and social profit was Rp2,740,642 per 1,000 birds. Private profit of partnership pattern with contract agreement was Rp707,381 and social profit was Rp3,898.950.  Private profit of partnership pattern with verbal agreement was Rp845,200 and social profit was Rp1,491,519.  Based on the analysis competitiveness, it showed that broiler chicken farm in South Lampung Regency had competitive and comparative advantages, in which PCR and DRCR value 0.38; 0,37 (autonomous pattern), 0.75; 0,35 (contract agreement pattern) and 0.69;0,56 (verbal agreement pattern). Elasticity value showed that competitiveness of broiler chicken farming in South Lampung Regency was sensitive with the price of broiler chicken and also price of broiler feed.Key words: Broiler chicken, competitiveness, PAM (Policy Analysis Matrix)